(untitled) (Revista Brasileira Multidisciplinar, 2022)
Desalination consists of removing salts from brackish water or seawater. Among the various known water desalination methods, the main ones are thermal and membrane, where reverse osmosis is the most common, and by electrodialysis. Water desalination is an alternative to the water supply that intends to meet the demands for drinking water. The aim of this study was to carry out a technological prospecting for patents related to water desalination. The following online patent databases were consulted: National Institute of Industrial Property (INPI), World Intellectual Property Organization (WIPO) and European Patent Office (EPO) using various descriptor terms. With the results obtained, surveys were made chronological period of filing, distribution of patents by countries and classification of patents according to the International Patent Classification (IPC). It was found that the WIPO database had the largest number of filed patents (208,425), followed by EPO (190,906) and INPI (118). According to IPC, most patents had these classifications: 52.91% include section C (Chemistry; Metallurgy), followed by section B (Performing operations; Transporting) with 39.84%. The largest number of patents occurred in 2019, with 3,026 filings, with the United States of America and China holding the largest number of registered patents. Faced with the scenario of world population growth and climate change, the promotion of new technologies that recycle water presents a promising alternative.